STAGGERED GRID METHOD FOR TWO DIMENSIONAL SHALLOW WATER EQUATIONS - Nuryaman, Toni
The shallow water equations are the common model to describe uid ow in rivers, channels, and coastal areas. To solve the equations numerically, several methods can be applied, one such methods is the staggered grid scheme. In this scheme , u and v are calculated at dierent grid points. So, approximation of , u and v should be calculated on dierent cells, i.e mass cell, momentum-x cell and momentum-y cell respectively. The non linear terms can be calculated using the rst order upwind scheme or the second order super bee scheme. Furthermore, the scheme is used to simulate a solitary wave propagate over a conical island. This simulation is to validate the numerical scheme. Next, the scheme is used to simulate the uid movement in a closed lake due to wind friction. In this simulation, several external forces such as wind force and bottom friction are incorporated.